Integration of renewable energy for sustainable electric vehicle charging in Sidoarjo, Indonesia: a techno-economic perspective - Mochamad Choifin; Yuki Trisnoaji; Zainal Arifin; Mochamad Subchan Mauludin; Marsya Aulia Rizkita; Singgih Dwi Prasetyo; Dony Perdana (International Journal of Applied Power Engineering (IJAPE), 2026)
This study explores the techno-economic feasibility of integrating solar photovoltaic (PV) systems for electric vehicle (EV) charging infrastructure in Sidoarjo, Indonesia. Through simulation using HOMER Pro software, both standalone PV and PV-grid hybrid configurations were evaluated under real-world EV load profiles. The analysis reveals that the PV-grid hybrid system demonstrates superior economic performance, achieving an annual energy production of 39,214 kWh, a levelized cost of energy (LCOE) of $0.3975/kWh, and a return on investment (ROI) of 62.01% over 20 years, despite a payback period exceeding 30 years. Sensitivity analysis confirms that the system remains moderately resilient under a 10% reduction in solar irradiance or a 20% increase in EV demand. The study also compares the standalone PV configuration, which, while suitable for off-grid applications, results in significant energy underutilization. Moreover, the PV-grid model supports surplus electricity sales, enhancing financial viability. These findings provide actionable insights for stakeholders, energy planners, and policymakers aiming to scale EV charging infrastructure sustainably in Indonesia’s urban environments.